Peran Strategis Jaminan Mutu dalam Meningkatkan Mutu Pendidikan melalui Pendekatan Manajemen Mutu Terpadu - Saleh, Abd. Rahman; Ramli, Rosmiati; Syamsuriah, Syamsuriah; Suherni, Suherni; Jupri, Jupri; Mulias, Ismail (Sulawesi Tenggara Educational Journal, 2025)
Educational quality is a critical indicator in determining the success of national education implementation. Achieving quality requires a consistent and continuously improving system. Quality assurance plays a strategic role in ensuring that all educational components operate according to established standards. One widely adopted approach is Total Quality Management (TQM), which emphasizes the collective participation of all organizational members to achieve optimal quality. This literature study aims to analyze the strategic role of educational quality assurance through the TQM approach in the context of improving the quality of education in Indonesia. The study employed a literature review method using scientific articles, reference books, and research reports published in the last ten years. The results indicate that applying TQM principles—such as customer focus (students), strong leadership, involvement of all stakeholders, process-based approaches, and continuous improvement—is highly relevant in the educational system. A structured quality assurance strategy can enhance school management effectiveness, teacher performance, and student satisfaction. This study recommends integrating the quality assurance system into national education policies and strengthening the culture of quality within educational institutions